Expanding the trait-based concept of benthic diatoms: Development of trait- and species-based indices for conductivity as the master variable of ecological status in continental saline lakes - Stenger-Kovács, Csilla; Körmendi, Kitti; Lengyel, Edina; Abonyi, András; Hajnal, Éva; Szabó, Beáta; Buczkó, Krisztina; Padisák, Judit (Ecological indicators, 2018)
[Display omitted] •Shallow, saline inland lakes carry high biological conservation values.•Species- and a trait-based diatom indices were developed for these ecosystems.•Both approaches can be applied in the ecological status assessment of soda pans.•Diatom ecological guild concept was adapted and further improved.•The developed trait-based index can be used independently of geographic location. Shallow, saline inland lakes occur over large areas in Central-Europe and they bear exceptionally high biological conservation values. Climate change and anthropogenic activities threaten their natural conditions, or even their existence. These aquatic ecosystems are exposed to multiple stress like naturally high conductivity, pH and nutrient load with very low transparency for light. As they are subjects of criteria set by the EC Water Framework Directive and biological conservation managment, there is an urgent need for developing a suitable quality index for their ecological status assessment. As one major Biological Quality Element, benthic diatoms may provide a reliable basis for their ecological status indication. Here, in a large data set covering the soda lakes of the Carpathian basin, we developed a species- and a trait-based diatom ecological status index. First, based on the weighted average method, we developed a type specific, species-based diatom index (DISP = Diatom Index for Soda Pans) using conductivity as master variable of environmental constrains; and therefore the ecological status in soda lakes. Furthermore, by adapting and improving further the widely-used diatom ecological guild concept, we also developed an alternative trait-based index, which helps avoiding some limitations arising from the obvious complexity of the taxonomy-based approach. Our DISP index covered a significantly larger species pool for index calculation, and responded to conductivity in a more reliable way compared to other available indices. In the trait-based index (TBI) motility, small cell size, and less roundish, more elongated shape as functional and morphological traits indicated pristine ecological conditions (i.e high conductivity) of the soda pans. Planktic life form, high and low ecological guild profiles, as well as the large cell size indicated worse ecological conditions (e.g. lower conductivity). Our study highlights that benthic diatoms provide a reliable basis for ecological status assessment in soda lakes. While both the taxonomic and the functional trait approaches performed well in our analysis, the success of the trait-based approach may enable the use of our TBI index in biomonitoring and conservation management of soda lakes outside of the Carpathian basin, independently of the geographic location.